Interpreting DNA Evidence : Statistical Genetics for Forensic Scientists - Evett, Ian Weir Weir, Bruce S (Sinauer Associates, 1998)
Interpretation of DNA profile matches depends on the use of statistical weights. This text provides the background information in statistics and genetics for the reader to arrive at these weights.